Geography of Anthropology, World Milieu, and Class: A Contextual Study of Nepal - Pokhrel, Kapil Dev (Journal of Durgalaxmi, 2025)
The present world is experiencing different kinds of new phenomena, such as neoliberalism and its impact globally, which have deeply affected human society. This article aims to explore the geography of anthropology in the changing context of neoliberal globalization, viz-a-viz. Nepal and the world. The article investigates why anthropology is appropriate to study classes in a neo-liberal context, how neo-liberalism affects the social life of humans, and how the classes are formed. It argues that anthropology, through its origin, focused on the study of others’ cultures, while its contemporary extent has expanded to the study of human society, various development paradigms, and its effects on men that include the study of class and culture in a globalized world shaped by neoliberalism. Methodologically, this article is based on a textual review of relevant literature in anthropology, blending with the essence of globalization and neoliberalism, while the ethnographic insights from central Nepal, as well as the author's own experiences, are also reflected. The findings suggest that neoliberal globalization has a profound impact on human societies, transforming traditional agrarian structures into proletarianization, often driven by dependence on remittance economies and overseas employment. Ultimately, the article highlights anthropology’s role in understanding the complex and shifting dynamics of class in the contemporary globalized world.